Acceptance and diffusion of hybrid corn seed in Vojvodina/Serbia - Janković, Dejan; Milić, Dragan; Novakov, Marina (Sociološki pregled, 2022)
The paper analyzes the modernization process of agricultural production in Serbia/Vojvodina, observed through the intensification of mercantile corn production that takes place by introducing the genetics of high-yielding seeds. This process is analyzed for the period of last 20 years through the theoretical-hypothetical framework of the theory of diffusion of innovations, in this case, the diffusion of seeds of non-Serbian seed companies (after 2000), which resulted in more intensive production, higher yields and different production practice of farmers in Serbia. The empirical research was conducted on a sample of 110 farmers and very similar to previous research on this topic, proved the innovativeness of certain producer groups and the relations between the diffusion of this innovation and the size of farms, values, habits and behaviour patterns of farmers.
Keywords: diffusion of innovation; hybrid corn seed; modernization of agriculture